Equilibrium and Kinetic Studies of Trihalomethanes Adsorption onto Multi-walled Carbon Nanotubes - Dehghani, Mohammad Hadi; Mohammadi, Mohammad; Mohammadi, Mahmood Ali; Mahvi, Amir Hossein; Yetilmezsoy, Kaan; Bhatnagar, Amit; Heibati, Behzad; McKay, Gordon (SPRINGER, 2016)
In the present study, multi-walled carbon nanotubes (MWCNTs) have been used for the rapid removal of four trihalomethanes (THMs) from aqueous solutions. The adsorption capacity of THMs onto MWCNTs was reasonably constant in the pH range of 5-7 but decreased as the pH exceeded 7. Four equilibrium isotherm models, namely, Langmuir, Freundlich, Temkin, and Sips, were applied to determine the best-fit equilibrium expressions. The results showed that all four experimental adsorption isotherms were best correlated by using the Sips model. The maximum adsorption capacities for the CHCl3, CHCl2Br, CHClBr2, and CHBr3 were found to be 10.98, 6.85, 6.57, and 5.95 mg/g, respectively. The rate of adsorption followed the pseudo-second-order kinetic model. Furthermore, four nonlinear regression-based equations were also derived to model THM adsorption from aqueous solutions by MWCNTs. The modeling results clearly indicated that the empirical formulations satisfactorily described the behavior of the present adsorption process for CHCl3 (R-2 = 0.949), CHCl2Br (R-2 = 0.945), CHClBr2 (R-2 = 0.936), and CHBr3 (R-2 = 0.919). The overall results confirmed that MWCNTs could be a promising adsorbent material for THMs removal from aqueous solutions.
Keywords: Multi-walled carbon nanotubes; Trihalomethanes; Adsorption isotherms; Modeling; DIVALENT METAL-IONS; AQUEOUS-SOLUTION; NATURAL PUMICE; COATED PUMICE; INTRAPARTICLE DIFFUSION; SORPTION; WATER; REMOVAL; PEAT; DYE; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources